Efficacy of novel phenoxyalkyl pyridinium oximes as brain-penetrating reactivators of cholinesterase inhibited by surrogates of sarin and VX. (25th November 2016) - Chambers, Janice E.; Chambers, Howard W.; Funck, Kristen E.; Meek, Edward C.; Pringle, Ronald B.; Ross, Matthew K.
Abstract: Pyridinium oximes are strong nucleophiles and many are effective reactivators of organophosphate-inhibited cholinesterase (ChE). However, the current oxime reactivators are ineffective at crossing the blood-brain barrier and reactivating brain ChE in the intact organism. Our laboratories have developed a series of substituted phenoxyalkyl pyridinium oximes (US patent 9, 227, 937 B2) with the goal of identifying reactivators effective in crossing the blood-brain barrier. The first 35 of the series were found to have similar in vitro efficacy as reactivators of ChE inhibited by a sarin surrogate (phthalimidyl isopropyl methylphosphonate, PIMP) or a VX surrogate (nitrophenyl ethyl methylphosphonate, NEMP) in bovine brain preparations as previously observed in rat brain preparations. A number of these novel oximes have shown the ability to decrease the level of ChE inhibition in the brains of rats treated with a high sublethal dosage of either a sarin surrogate (nitrophenyl isopropyl methylphosphonate, NIMP) or the VX surrogate NEMP. Levels of reactivation at 2 h after oxime administration were up to 35% while the currently approved therapeutic, 2-PAM, yielded no reduction in brain ChE inhibition. In addition, there was evidence of attenuation of seizure-like behavior with several of the more effective novel oximes, but not 2-PAM. Therefore these novel oximes have demonstrated an ability to reactivate inhibited ChE in brain preparations from two species and in vivo data support their ability to enter the brain and provide a therapeutic action. These novel oximes have the potential to be developed into improved antidotes for nerve agent therapy. Highlights: Novel oximes reduce brain cholinesterase inhibition after sublethal doses of OPs. Novel oximes attenuate seizure-like behavior after sublethal doses of OPs. 2-PAM does not reduce cholinesterase inhibition or attenuate seizure-like behavior. Novel oximes have promise as improved nerve agent therapeutics.